Maternal toxicity and teratogenic effects of Jatropha curcas L. crude oil in pregnant Sprague dawley rats - Samat, Yon Thannia (2013)
Jatropha curcas (L.) (Euphorbiaceae), ia a large shrub, attaining 3-4 m in height, common in Brazil and also found in India and Africa in semi-wild conditions. Laboratory studies on the effects of Jatropha curcas on pregnancy is limited and the number of experimental animals used in most studies were insufficient for any firm conclusions to be drawn. Research however has shown that it is has pregnancy terminating effects in rats and was used widely in some African countries for contraceptive intentions. Feeding studies also showed that the whole seeds were highly toxic. Curcin, a toxic protein isolated from the seeds, inhibits protein synthesis in in vitro studies even though it is less toxic than ricin and abrin. The oil of Jatropha contain irritant phobol esters which causes purgative and skin irritant effects and possess tumour-promoting (co-carcinogenic) properties. In this study, pregnant Sprague-Dawley rats were administered Jatropha crude oil (JCO) orally at doses of 0.175, 0.35 or 0.7 g/ml during embryogenesis (Gestation day (GD) 1-7) for early gestation group and during organogenesis on GD 8-14 for late gestation group to examine any toxic effects. On day 21st of pregnancy, the rats were anesthetized with chloroform. Ovaries and uteri were removed by Caesarean section. Heart, ovaries, placenta, liver, intestines, stomach, kidneys, and lungs of dams were collected for obvious external malformations before subjected to fetal staining to assess teratogenic effects. Placentas were stored in 10% buffered formalin for subsequent histopathology examination to observe effects of JCO on placental morphology. Results were reported as means + S.E.M. Data were analysed with SPSS. Two-way ANOVA followed by Duncan post hoc test were used to determine the degree of significance for the various mean variables obtained and p < 0.05 was considered significant. Body weight of rats exposed to JCO at does to 0.35 and 0.7 g/ml examined weresifnificantly lower (p < 0.05)than those of controls who only received corn oil. No foetuses were observed with external malformations in this study but for skeletal malformations, variations or abnormalities observed in foetuses from treated groups include dumbbell shape vertebrae, split vertebrae, wavy ribs, poorly ossified sternum and xiphisternum and hypoplastic sternum. Placentas of rats exposed to JCO showed histological changes in maternal-fetal interface, trophoblastic giant cell layers, and labyrinth layer with an increase in abnormal trophoblastic giant cells which has atypical shape with pyknotic and irregular nuclei. The results of this study indicate that JCO causes acute toxicity to the dams, induce teratogenic effects on foetuses and stimulate deleterious effects on palcenta.